Utilisation of Kinemaster Application as Thematic Learning Media Development in Elementary School - Patry, Him; Kadir, Muhammad Ahyar; Ritonga, Abdillah Rofiif Fatin (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Thematic learning at Al-Bina 01 Koto Baru IT Elementary School during the co-19 pandemic has decreased in terms of quality and in the learning process. After research, this happened because of the lack of effectiveness of the learning process and the teacher's lack of optimization in conveying information related to learning material. Purpose. The purpose of this research is to create learning media for students so that teachers are easy to teach lessons and lessons become more interesting so that students are more enthusiastic in learning. Method. The method applied in this research is based on the use of descriptive research methods. By using data analysis on the comparison of student grades carried out through collecting samples of thematic learning scores of a group of students at Al-Bina 01 Koto Baru Integrated Islamic Elementary School during face-to-face learning before the covid-19 pandemic and online learning after the covid-19 pandemic took place. Results. The results of this study After the operation of this thematic learning video media to students, the survey proved that with the learning media video, the quality of student learning outcomes at Al-Bina 01 Koto Baru IT Elementary School has increased. Conclusion. Based on the research and explanations above, it can be concluded that the positive and negative impacts of the covid-19 pandemic are very influential on the world of education. Especially the impact on the quality of education in Indonesia which occurs due to the forced change in the learning system from face-to-face to online learning throughout Indonesia.